2020
DOI: 10.1186/s13063-020-04619-1
|View full text |Cite
|
Sign up to set email alerts
|

Home Treatment of Older People with Symptomatic SARS-CoV-2 Infection (COVID-19): A structured Summary of a Study Protocol for a Multi-Arm Multi-Stage (MAMS) Randomized Trial to Evaluate the Efficacy and Tolerability of Several Experimental Treatments to Reduce the Risk of Hospitalisation or Death in outpatients aged 65 years or older (COVERAGE trial)

Abstract: Objectives To assess the efficacy of several repurposed drugs to prevent hospitalisation or death in patients aged 65 or more with recent symptomatic SARS-CoV-2 infection (COVID-19) and no criteria for hospitalisation. Trial design Phase III, multi-arm (5) and multi-stage (MAMS), randomized, open-label controlled superiority trial. Participants will be randomly allocated 1:1:1:1:1 to the following strategies: Arm 1: Control arm Arms 2 to 5: Experimental treatment arms Planned interim analyses will be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…DPP-4i, another commonly used antidiabetic drug, might not protect people from infection as reported in a large case-control study in which DPP-4i was more prevalent in diabetic patients with confirmed COVID-19 than those without COVID-19, but might still play an important role in protecting COVID-19 patients from organ failure and evolving pneumonia to pulmonary fibrosis ( 13 ). A clinical trial is ongoing in France to assess the efficacy of several repurposed drugs against COVID-19 including repaglinide ( 14 ). A propensity-score-matched cohort study also noted the influence of SGLT-2i on susceptibility to COVID-19 in diabetic patients ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…DPP-4i, another commonly used antidiabetic drug, might not protect people from infection as reported in a large case-control study in which DPP-4i was more prevalent in diabetic patients with confirmed COVID-19 than those without COVID-19, but might still play an important role in protecting COVID-19 patients from organ failure and evolving pneumonia to pulmonary fibrosis ( 13 ). A clinical trial is ongoing in France to assess the efficacy of several repurposed drugs against COVID-19 including repaglinide ( 14 ). A propensity-score-matched cohort study also noted the influence of SGLT-2i on susceptibility to COVID-19 in diabetic patients ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…DPP-4i, another commonly used antidiabetic drug, might not protect people from infection as reported in a large case-control study in which DPP-4i was more prevalent in diabetic patients with confirmed COVID-19 than those without COVID-19, but might still play an important role in protecting COVID-19 patients from organ failure and evolving pneumonia to pulmonary fibrosis(17). A clinical trial is ongoing in France to assess the efficacy of several repurposed drugs against COVID-19 including repaglinide(18). A propensity-score-matched cohort study also noted the influence of SGLT-2i on susceptibility to COVID-19 in diabetic patients(19).…”
Section: Introductionmentioning
confidence: 99%
“…[21] [22] Few outpatient trials for non-anticoagulation and nonvaccine related studies are ongoing. [23] However, prospective randomized trials on COVID-19…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…21,22 Few outpatient trials for nonanticoagulation and nonvaccine-related studies are ongoing. 23 However, prospective randomized trials on COVID-19 patients are pending and largely overlook the potential of pulmonary endothelial cells as a therapeutic target. 24,25 With this premise, we decided to evaluate whether sulodexide's pleiotropic properties prevent the SARS-CoV-2mediated endothelialitis with hypercoagulability and inflammation.…”
Section: Introductionmentioning
confidence: 99%